2011
DOI: 10.1038/bjc.2011.310
|View full text |Cite
|
Sign up to set email alerts
|

How do patient and hospital features influence outcomes in small-cell lung cancer in England?

Abstract: Background:Our aim was to systematically determine how features of patients and hospitals influence access to chemotherapy and survival for people with small-cell lung cancer in England.Methods:We linked the National Lung Cancer Audit and Hospital Episode Statistics and used multiple logistic and Cox regression analyses to assess the influence of patient and hospital features on small-cell lung cancer outcomes.Results:There were 7845 patients with histologically proven small-cell lung cancer. Sixty-one percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 23 publications
3
54
3
Order By: Relevance
“…prior research involvement in general, nor membership of the network, but not in the specific trial, made an impact. Some differences between the hurdles needed to cross to implement the respective drug and behavioural treatments might explain the differences 'comparatively farther along the "S-shaped curve" that characterises the diffusion of innovations (Rogers, 1995 Of the 21 papers in the by-product category described above, 17 97,99,[101][102][103][104][105]107,108,[110][111][112][113][114][115][116][117] produced positive findings about the link between research engagement and improved performance. We classified seven of the positive studies as important to our review.…”
Section: By-product Papersmentioning
confidence: 99%
See 4 more Smart Citations
“…prior research involvement in general, nor membership of the network, but not in the specific trial, made an impact. Some differences between the hurdles needed to cross to implement the respective drug and behavioural treatments might explain the differences 'comparatively farther along the "S-shaped curve" that characterises the diffusion of innovations (Rogers, 1995 Of the 21 papers in the by-product category described above, 17 97,99,[101][102][103][104][105]107,108,[110][111][112][113][114][115][116][117] produced positive findings about the link between research engagement and improved performance. We classified seven of the positive studies as important to our review.…”
Section: By-product Papersmentioning
confidence: 99%
“…102,110,111,113,[114][115][116] Four papers 98,100,106,109 produced negative, or mixed/negative, findings and we classified two of these as important. 98,109 Most of the 17 papers 97,99,[101][102][103][104][105]107,108,[110][111][112][113][114][115][116][117] reporting positive findings described measurable improvements in the processes of care thought to lead to better outcomes, rather than better health outcomes per se. Just six studies reported better health outcomes, three of which had been included in Clarke and Loudon's review (du Bois et al, 102 Jha et al 105 and Majumdar et al…”
Section: By-product Papersmentioning
confidence: 99%
See 3 more Smart Citations